A Study on Dental and Oral Health Knowledge and Behavior of Fourth to Sixth Graders in Gunung Bahagia, Balikpapan. - Ahmad Fadillah; Lilies Anggarwati; Verry Asfirizal; Sylvia Agustin (Universitas Mulawarman, 2026)
Dental and oral problems, especially dental caries, can be influenced by several crucial factors, e.g., environment, health care, behaviour, knowledge, and heredity. Knowledge and behaviour are imperative and have a part in determining the dental care and dental hygiene of a person. According to the data from Basic Health Research (Riset Kesehatan Dasar – Riskesdas) of 2018, 96.5% of children aged 10-14 had brushed their teeth daily, but only 2.1% knew and could brush their teeth at the right time. Objective: to investigate the knowledge level and dental and oral care behaviour, in elementary school students in grades IV-VI. Methods: This research is a quantitative research with the sampling method used is proportionate stratified random sampling. The data collection technique used a questionnaire distributed to elementary school students in grades IV-VI. Results: From 311 samples consisted of elementary students grade IV-VI in Gunung Bahagia Ward, 97.4% (n=303) of the samples had good level of knowledge and 48.9% (n=152) of the samples had moderate category in dental and oral care behaviour. Conclusion: The level of knowledge and behavior of dental and oral health care for elementary school students in grades IV-VI in Gunung Bahagia, Balikpapan City is in good condition.